Development of Discovery Learning-Based Booklets as Learning Media for Human Digestive System Material - Halifa, Qiara Nur; Fauziah, Nurul (Journal Of Biology Education Research (JBER), 2025)
Science learning plays an essential role in helping students develop a comprehensive understanding of natural phenomena and biological processes. However, observations and interviews with teachers and students revealed that the classroom learning process often relied on lecture-based and textbook-centered methods, which tended to make students less enthusiastic and less active during lessons. Therefore, this study aimed to develop a discovery learning- based booklet as a learning medium for the human digestive system material. This research is a development study that employed the Plomp development model. Data collection instruments included teacher and student interview sheets, observation sheets, needs analysis questionnaires, self evaluation forms, validation sheets, and practicality test questionnaires through one-to-one evaluations, small group trials, and field testing. The results of expert validation showed that the developed booklet met the criteria for validity in terms of content, design, and learning feasibility. Furthermore, the practicality test results demonstrated that the booklet was easy to use, engaging, and well received by both teachers and students. In conclusion, the discovery learning-based booklet on the human digestive system is feasible and practical to be used as a learning medium in junior high school science classes.